¿Cómo administrar los recursos de un parque nacional natural de tal manera que su atractivo turístico aumente? : caso de estudio: PNN Chingaza (2017)
"This project tries analyze from the system dynamics perspective the resources allocation problem in PNN Chingaza park. There are 5 mayor expenses and managing office has to decide how budget is distributed in these. This social system has many actors that take decisions according to their goals and this situation results in a system dynamic where more budget is needed each year to maintain the yearly visitors level constant. After conceiving the problem as system dynamic, an intervention policy is designed to solve the problematic situation." -- Tomado del Formato de Documento de Grado.